Smart Grids Technology and Applications - Mihet-Popa, Lucian (IntechOpen, 2023)
This book provides a comprehensive overview of smart grid technology. It contains six chapters organized into three sections: "AC-DC Smart Hybrid Microgrid: Modelling, Control and Applications", "Smart Distribution Systems: Methodologies, Realtime Platforms and Testing Methods", and "Energy Storage Systems and Their Applications in Smart Grids". Chapters address such topics as the advantages and disadvantages of AC/DC hybrid microgrids, DER components in an AC microgrid, methodologies for solving the reconfiguration and reactive power compensation dispatch in a smart distribution network, digital twin types, the different types of energy storage systems, and much more.